Advancing human resource project management - Klimoski, Richard J. (San Francisco : Jossey-Bass & Pfeiffer Imprints, Wiley, 2014)
'Get real-world solutions and evidence-based guidelines for HR project management challengesTackling major human resources management projects can be daunting, but now you can learn from the lessons of HR professionals who have encountered roadblocks or challenges in similar contexts. Advancing Human Resource Project Management is an in-depth, thoughtful resource that highlights the knowledge and experience of those who have undertaken large HR projects. This guide illustrates what worked and what didn't, with a focus on evidence and real-world cases to illuminate effective strategies and solutions. Each chapter presents empirical findings complemented by professional judgment and wisdom from human resource management professionals well-versed in global business environments. Advancing Human Resource Project Management recognizes the importance of context, addresses the practical and professional implications of managing HR management projects in different industry sectors, and provides comprehensive coverage on implementing global development programs and project initiation and planning. Ideal for global Industrial and Organizational Psychology faculty and practitioners, graduate students, and, especially, HR professionals, this resource uncovers the best evidence-based practices available today for effective HR project management strategies. The book includes: An emphasis on the implications and challenges of providing solutions for HR business problems on a global scale Real-world cases and firsthand professional experiences with summaries of knowledge gained from research and practice Advice on tackling challenges inherent in various stages of a project Expertise and counsel from HR professionals familiar with large projects and from those who study and work in the field of project management Let this comprehensive resource guide your approach to initiating and managing large HR projects. With solid, empirical evidence and relatable case studies, Advancing Human Resource Project Management is the ideal professional companion for those looking to strengthen their project techniques, project leadership, and management skills'--
'Addresses the implications and challenges of providing solutions for HR business problems on a global scale. Provides real-world cases and firsthand professional experiences with summaries of knowledge gained from research and practice, advice on tackling challenges inherent in various stages of a project, and expertise and counsel from HR professionals familiar with large projects and from those who study and work in the field of project management'--
Ch. 1. Introduction / Richard J. Klimoski [and others] -- Part I. Case studies : context matters -- ch. 2. Redesigning Microsoft's high potential development experience / Shannon Wallis -- ch. 3. Litigation-driven human resource management changes / Suzanne Tsacoumis and Michelle Davis King -- ch. 4. Project A : five keys to management and scientific success / Michael G. Rumsey and Paul A. Gade -- ch. 5. Managing critical assessment and development components of a global leadership development program / Robin Cohen [and others] -- Part II. Fundamentals : transferable wisdom -- ch. 6. Preparing for an HR project / Ren Nygren and Scott Erker -- ch. 7. Project initiation / Reid Klion and Julia Bayless -- ch. 8. Planning and organizaing / Monique Aubry -- Effective HR project execution : understandnign project, team, and stakeholder issues / Peter A. Hausdorf, Stephen D. Risavy, and Philip E. Hunter -- ch. 10. Contracts administration for HR practitioners / Macie Paynter, Kerri Ferstl, and Ryan O'Leary -- ch. 11. Maintaining security / Lucas Kuhlmann -- Part III. Applications : strategic issues -- ch. 12. Managing in a global environment / Terry Cooke-Davies -- ch. 13. The development of project management skills / Beverly A. Dugan -- ch. 14. Toward a comprehensive project stakeholder management approach for HR projects / Martina Huemann and Dagmar Zuchi -- ch. 16. The four Cs of human resource project teams : context, configuration, cycles, and challenges / Francois Chiocchio and Peter A. Hausdorf -- ch. 17. Knowledge management in the project context : what it means for HR projects / Francois Chiocchio, Carla Messikomer, and Christian Dagenais -- Ethics and governance in the temporary organization / Ralf Muller -- Part IV. Conlcusion -- ch. 19. HR project cases, fundamentals and applications : lessons learned and other advancements / Richard J. Klimoski [and others].
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
Keywords: Personnel management; Project management; Personnel management; Project management; Electronic books; Electronic books